Stereotactic Re-irradiation in Recurrent Prostate Cancer after Previous Postoperative or Definitive Radiotherapy: Long-term Results after a Median Follow-up of 4 Years. Issue 1 (January 2022) - Francolini, G.; Loi, M.; Di Cataldo, V.; Detti, B.; Stocchi, G.; Masi, L.; Doro, R.; Scoccimarro, E.; Bellini, C.; Aquilano, M.; Allegra, A.G.; Peruzzi, A.; et al.
Abstract: Aims: In 2018, we published early results from a cohort of patients treated with stereotactic body radiotherapy (SBRT) after previous radiotherapy with definitive or postoperative intent. We sought to provide extended follow-up of this cohort to confirm the safety and efficacy of this approach in a real-world scenario. Materials and methods: Fifty patients affected by local relapse after previous definitive or postoperative radiotherapy were treated with SBRT. Treatment provided a total dose of 30 Gy in five fractions. Data about biochemical relapse-free survival (BRFS) and metastasis-free survival (MFS), together with adverse events, were analysed. Toxicity was reported according to Common Terminology Criteria for Adverse Events (CTCAE) score v.4.03. Results: After a median follow-up of 48.2 months, the median BRFS was 43 months. A Gleason score >7 and concomitant androgen deprivation therapy were shown to be predictors of the worst BRFS (hazard ratio 2.42, 95% confidence interval 1.09–5.41, P = 0.02; hazard ratio 2.83, 95% confidence interval 1.17–6.8, P = 0.02, respectively). The median MFS was not reached; concomitant androgen deprivation therapy was confirmed to be predictive of the worst MFS (hazard ratio 4.75, 95% confidence interval 1.52–14.8, P = 0.007). Late grade 1 and 2 rectal and bladder toxicity occurred in three (6%) and 13 (26%) patients, respectively. One patient experienced both grade 3 acute and chronic bladder toxicity. Conclusion: Salvage SBRT re-irradiation after previous postoperative or definitive radiotherapy for local prostate cancer recurrence confirmed promising results in terms of oncological outcomes and the safety of this approach. Highlights: Long terms outcomes after reirradiation for prostate cancer. Promising biochemical control of disease after this approach. Low rate of reported adverse events after treatment. Gleason <7 significantly influencing clinical outcomes after treatment.